Referendum niepodległościowe w świetle opinii Sądu Najwyższego Kanady w sprawie secesji Quebecu z 1998 r. - Jacek, Adrianna; Glapiak, Aleksander (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Independence referendums taking place in territories that stand out against other regions of the country are considered the propitious way to intimate the wishes of their inhabitants. A lot of conflicts between the central government and striving for autonomy territories can be raised because of the lack of legal regulations in area of performing and considering those referendums. This type of disputation was under way in Canada till the turn of the 20th and 21th centuries. The unilaterally determined rules of Canadian referendum are continuingly mired in controversy even so that act of democracy was carried out twofold. They are also unequivocally targeted at the interests of Federation clearly unwilling to let the francofonic Quebec separate itself.
Keywords: większość; demokracja bezpośrednia; historia i kultura; sąd najwyższy; prowincje; Kanada; federacja; autonomia; prawo konstytucyjne; Clarity Act; referendum niepodległościowe; pytania referendalne